Critical physicochemical and biological attributes of nanoemulsions for pulmonary delivery of rifampicin by nebulization technique in tuberculosis treatment - Kifayatullah Shah; Lai Wah Chan; Tin Wui Wong (Taylor & Francis Group, 2017)
The study investigated aerosolization, pulmonary inhalation, intracellular trafficking potential in macrophages and pharmacokinetics profiles of rifampicin-oleic acid first-generation nanoemulsion and its respective chitosan- and chitosan-folate conjugate-decorated second and third-generation nanoemulsions, delivered via nebulization technique. The nanoemulsions were prepared by conjugate synthesis and spontaneous emulsification techniques. They were subjected to physicochemical, drug release, aerosolization, inhalation, cell culture and pharmacokinetics analysis. The nanoemulsions had average droplet sizes of 40-60 nm, with narrow polydispersity indices. They exhibited desirable pH, surface tension, viscosity, refractive index, density and viscosity attributes for pulmonary rifampicin administration. All nanoemulsions demonstrated more than 95% aerosol output and inhalation efficiency greater than 75%. The aerosol output, aerosolized and inhaled fine particle fractions were primarily governed by the size and surface tension of nanoemulsions in an inverse relationship. The nanoemulsions were found to be safe with third-generation nanoemulsion exhibiting higher cell internalization potential, reduced plasma drug concentration, and higher lung drug content.